A modification design method for the angular misalignment of the spline drum shaping - YUAN Xichuan; LIU Qi; TANG Jinyuan; LI Yuan; SU Hui (Jixie chuandong, 2025)
ObjectiveTo address the edge contact and uneven load distribution caused by angular misalignment in involute spline pairs, an efficient optimal design method based on contact mechanical characteristics was proposed, overcoming the limitations of the low efficiency in traditional trial-and-error crowning modification approaches.MethodsFocusing on angular misaligned involute spline pairs, analytical prediction formulas for tooth contact regions under different modification amounts were established through analysis of contact extrusion deformation characteristics in drum-shaped splines. Computational samples were generated by setting varying modification amounts, revealing the correlation between maximum contact stress (Pmax) and tooth surface modification. The optimal modification design for Pmax minimization was achieved by analyzing contact region features in the minimum-Pmax sample and combining them with the established prediction formulas. Finite element simulation and test verification were subsequently conducted to validate the accuracy and effectiveness of this method.ResultsThe analytical results demonstrate that regarding computational efficiency, the proposed method reduces finite element simulations from 6-10 iterations required by traditional trial-and-error approaches to a single simulation for determining optimal modification, achieving over 80% efficiency improvement; in performance enhancement, the optimized modification demonstrates 30.22% reduction in contact stress and 50% decrease in maximum tooth wear volume under misalignment conditions, effectively eliminating edge contact while significantly extending service life.